Pengaruh Pemberian Uap Etanol dan Emulsi Lilin Lebah Terhadap Mutu dan Masa Simpan Buah Salak Gulapasir - Ni Kadek Juliani; I Made Supartha Utama; I G.N.Apriadi Aviantara (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2017)
The aim of this study is to know the effect of ethanol vapor with different consentration and different concentration of beeswax emulsion, as a coating material that can preserve the quality and shelf life of salak Gulapasir. This research used a factorial randomized block design with two factors which are ethanol vapor treatment with 3 levels of concentrations (0%, 10% and 20%) and variety concentration of beeswax emulsion (0%, 1%, 2%, and 3%). Salak Gulapasir as control were prepared without treatment of ethanol vapor and beeswax emulsion, as a coating material. The experiment were devided into three groups. The observation is perfomed every five days until fifteenth day. The observed parameter of this research were weight loss, hardness, intensity of damage, total dissolved solids, total titrated acids, color difference and organoleptic test. The result of variance analysis showed that the interaction between ethanol vapor and beewax coating significantly affect the weight loss, hardness, intensity of damage, color difference, and organoleptic test. Whereas no significantly affect on total dissolved solids and total titrated acids. The combination of ethanol vapor of 20% (diluted in the water) and 1% concentration of beeswax emulsion as a coating material with the resulting characteristic weighted mean value of 21.04%, hardness 37.34 N, intensity of damage 6.79%, total dissolved solids 21, 04 0Brix, total acid 0.59%, color difference 26.14. Similarly, the organoleptic test has an average value of panelist for taste of 3.57, aroma 3.27, and color 3.51.